2010
DOI: 10.1152/ajpendo.00081.2010
|View full text |Cite
|
Sign up to set email alerts
|

Acute inflammation reduces kisspeptin immunoreactivity at the arcuate nucleus and decreases responsiveness to kisspeptin independently of its anorectic effects

Abstract: Tena-Sempere M. Acute inflammation reduces kisspeptin immunoreactivity at the arcuate nucleus and decreases responsiveness to kisspeptin independently of its anorectic effects. Am J Physiol Endocrinol Metab 299: E54 -E61, 2010. First published April 20, 2010 doi:10.1152/ajpendo.00081.2010.-Severe inflammatory challenges are frequently coupled to decreased food intake and disruption of reproductive function, the latter via deregulation of different signaling pathways that impinge onto GnRH neurons. Recently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 40 publications
2
32
2
Order By: Relevance
“…Thereafter, we and other groups have vigorously evaluated the effects of stress on the kisspeptin system and the neuroendocrine mechanisms that underlie these effects. In agreement with the findings of our aforementioned study, the administration of LPS decreased hypothalamic Kiss1 mRNA expression and kisspeptin immunoreactivity, and the co-administration of kisspeptin partially restored serum LH levels in female rats [76]. In addition, other kinds of stress, such as psychosocial, unpredictable chronic (six randomly assigned stressors), and hypoglycemic stress, also reduced hypothalamic Kiss1 mRNA expression and kisspeptin neuron activity [77][78][79].…”
Section: The Roles Of Kisspeptin In Stress-induced Hpg Axis Dysfunctionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thereafter, we and other groups have vigorously evaluated the effects of stress on the kisspeptin system and the neuroendocrine mechanisms that underlie these effects. In agreement with the findings of our aforementioned study, the administration of LPS decreased hypothalamic Kiss1 mRNA expression and kisspeptin immunoreactivity, and the co-administration of kisspeptin partially restored serum LH levels in female rats [76]. In addition, other kinds of stress, such as psychosocial, unpredictable chronic (six randomly assigned stressors), and hypoglycemic stress, also reduced hypothalamic Kiss1 mRNA expression and kisspeptin neuron activity [77][78][79].…”
Section: The Roles Of Kisspeptin In Stress-induced Hpg Axis Dysfunctionsupporting
confidence: 91%
“…As a result, it was found that both the central administration of CRH and the peripheral administration of corticosterone reduced hypothalamic Kiss1 mRNA expression and kisspeptin neuron activity in female rats and mice, indicating that activation of the HPA axis is involved in the stressinduced suppression of the kisspeptin system [77,80]. Interestingly, relatively severe stress protocols were used in these studies; i.e., high-dose LPS (1-5 mg/kg) or repeated LPS administration protocols (three consecutive injections at 24-h intervals), to evaluate the effects of immune stress [75,76,81,82], and chronic (once per day for four weeks) or combined (restraint and isolation) protocols were used to evaluate the effects of unpredictable and psychosocial stress [78,79]. Similarly, we found that a subseptic dose (500 μg/kg) of LPS did not affect hypothalamic Kiss1 mRNA expression in female rats, indicating that only chronic or severe stress affects the kisspeptin system [81,82].…”
Section: The Roles Of Kisspeptin In Stress-induced Hpg Axis Dysfunctionmentioning
confidence: 99%
“…The results of other studies examining the effect of food restriction or fasting, and the associated decrease in circulating leptin concentrations, have provided no evidence of a reduction in the ability of kisspeptin to induce LH secretion. For example, in prepubertal fasted rats (Castellano et al 2005) and food-restricted male rats (Castellano et al 2010), i.c.v. kisspeptin administration has been shown to result in an increased release of LH compared with that in the AL-fed controls.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of LPS on the expression of hypothalamic mRNA levels of Kiss1 and systemic levels of LH is fully reversed by indomethacin, a nonsteroidal anti-inflammatory drug. Moreover, it was observed that exogenous KP injection greatly increased systemic levels of LH in LPS-injected animals just like placebo animals (Iwasa et al 2008, Castellano et al 2010b). These results suggest that KP-containing cells are highly sensitive to immune/inflammatory challenges and convey these signals to the network of GnRH-containing neurons in the hypothalamus.…”
Section: Infection/immune Challenge Induced Malnutrition-related Altementioning
confidence: 92%
“…Lipopolysaccharide (LPS) administration has been shown to greatly decrease the hypothalamic levels of Kiss1 mRNA and reduce systemic levels of LH in gonadectomized rats (Iwasa et al 2008, Castellano et al 2010b. The inhibitory effect of LPS on the expression of hypothalamic mRNA levels of Kiss1 and systemic levels of LH is fully reversed by indomethacin, a nonsteroidal anti-inflammatory drug.…”
Section: Infection/immune Challenge Induced Malnutrition-related Altementioning
confidence: 99%